ỨNG DỤNG PLASMA ĐIỆN HÓA TRÊN ĐIỆN CỰC SẮT XỬ LÝ NƯỚC THẢI TỪ CÁC PHÂN TÍCH XÉT NGHIỆM HÓA, SINH CỦA BỆNH VIỆN - Nguyễn, Đức Hùng; Phạm, Hoàng Long; Trần, Văn Công (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
APPLICATION OF ELECTROCHEMICAL PLASMA ON IRON ELECTRODES FOR TREATING WASTEWATER FROM CHEMICAL AND BIOCHEMICAL ANALYIS OF HOSPITALSAnalysis of chemical and biochemical from hospitals and health facilities used blood, urine of patients as well as a variety of solvents and chemical compounds created hazardous wastewater that must be treated before discharge into the environment. Application of electrochemical plasma on iron electrodes would generating an ionizing environment and zero valence iron nano that could treating quickly and effectively pollutants in wastewater after analyzing process and biochemical testing of hospitals. After each electrochemical plasma treatment on iron electrodes, the environmental characteristics such as electrical conductivity and pH change a little, but the COD, TDS, NH4+ ratios decreased significantly from 94.6%; 69.9% to 68.8%, respectively. Only after 3 times consecutive treatment, each time was 60 minutes, the environmental parameters have achieved the requirements of National technical regulation on health care wastewater - QCVN 28:2010/BTNMT, which is issued by Ministry of Natural Resources and Enviroment, Vietnam.